2010
DOI: 10.1016/j.jaad.2009.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Acral lesions in tuberous sclerosis complex: Insights into pathogenesis

Abstract: Background-Patients with tuberous sclerosis complex (TSC) are predisposed to developing ungual fibromas and other acral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
0
47
0
4
Order By: Relevance
“…Molecular genetic data are lacking, but rare cases have been associated with Rb aberrations. 9,10,12,13 Various techniques have been proposed for excising difficult lesions. 11 Fibro-osseous pseudotumor of digits Fibro-osseous pseudotumor of digits may become absorbed by the umbrella term myositis ossificans, to which it is microscopically nearly identical.…”
Section: Fibroma Of Tendon Sheathmentioning
confidence: 99%
“…Molecular genetic data are lacking, but rare cases have been associated with Rb aberrations. 9,10,12,13 Various techniques have been proposed for excising difficult lesions. 11 Fibro-osseous pseudotumor of digits Fibro-osseous pseudotumor of digits may become absorbed by the umbrella term myositis ossificans, to which it is microscopically nearly identical.…”
Section: Fibroma Of Tendon Sheathmentioning
confidence: 99%
“…Periungual and subungual fibromas, or Koenen tumors, commonly occur in patients with tuberous sclerosis, with an incidence of 15% to 52% in this population. 24 Onset typically occurs between the second and fifth decades 24 ; there have been reports of incidence as high as 88% in patients over age 30. 9 A recent study of 76 patients (all female) with tuberous sclerosis found 61 patients to have ungual fibromas; periungual tumors were more common than tumors in the subungual region.…”
Section: Soft Tissue Neoplasms Fibromamentioning
confidence: 99%
“…Some patients described preceding trauma before the development of ungual fibromas; however, the exact etiology remains unknown. 24 Large subungual fibromas present as pink papules originating from under the nail plate, which may cause lifting of the nail plate with visible hyperkeratosis (Fig. 8).…”
Section: Soft Tissue Neoplasms Fibromamentioning
confidence: 99%
See 1 more Smart Citation
“…Su localización en la zona periungueal puede provocar anomalías en la lámina ungueal Las presiones del calzado favorecen el crecimiento del tamaño de las lesiones de las uñas, siendo los traumatismos los que desencadenan la formación de estos tumores 12 . No existe una etiopatogenia clara de esta patología, si bien el factor traumático puede influir en el crecimiento de la lesión 14,15 .…”
unclassified